NEW SYSTEM ECONOMICS(A SENIOR SECONDARY COURSE) - Udu Ewa et al (Africana- Fep Publishers Limited, 1989)
It is designed particularly for candidates who are preparing for the Senior School Certificate examination conducted by the West African Examination Council and for the Joint Admission and Matriculation Board (JAMB)examination.
Keywords: Economics- Education